Invasion potential of hornets (Hymenoptera: Vespidae: Vespa spp.) - Otis, Gard W.; Taylor, Benjamin A.; Mattila, Heather R. (Frontiers in Insect Science, 2023)
Hornets are large, predatory wasps that have the potential to alter biotic communities and harm honey bee colonies once established in non-native locations. Mated, diapausing females (gynes) can easily be transported to new habitats, where their behavioral flexibility allows them to found colonies using local food and nest materials. Of the 22 species in the genus Vespa, five species are now naturalized far from their endemic populations and another five have been detected either in nature or during inspections at borders of other countries. By far the most likely pathway of long-distance dispersal is the transport of gynes in transoceanic shipments of goods. Thereafter, natural dispersal of gynes in spring and accidental local transport by humans cause shorter-range expansions and contribute to the invasion process. Propagule pressure of hornets is unquantified, although it is likely low but unrelenting. The success of introduced populations is limited by low propagule size and the consequences of genetic founder effects, including the extinction vortex linked to single-locus, complementary sex determination of most hymenopterans. Invasion success is enhanced by climatic similarity between source locality and introduction site, as well as genetic diversity conferred by polyandry in some species. These and other factors that may have influenced the successful establishment of invasive populations of V. velutina, V. tropica, V. bicolor, V. orientalis, and V. crabro are discussed. The highly publicized detections of V. mandarinia in North America and research into its status provide a real-time example of an unfolding hornet invasion.